Beyond the invisible hand: groundwork for a new economics - Basu, Kaushik (London, 2010)
One of the central tenets of economics is that, given certain conditions, selfinterested behavior by individuals leads them to the social good, almost as if orchestrated by an invisible hand. However, over the past two centuries, this proposition first put forth by Adam Smith has been taken out of context, contorted, and used as the cornerstone of free-market orthodoxy. In Beyond the Invisible Hand, Kaushik Basu lays bare the implications of this gross misrepresentation of Smith$1 (Bs theory which, he argues, has resulted in hampering our understanding of how economies function, why some economies fail and some succeed, and what the nature and role of state intervention might be. Comparing this view of the invisible hand to the vision described by Kafka$1 (Bin which individuals pursuing their atomistic interests, devoid of moral compunction, end up creating a world that is mean and miserable$1 (BBasu calls for collective action and the need to shift our focus from the efficient society to one that is also fair. As Basu pointedly reminds us, by ignoring the role of culture and custom, traditional economics promotes the view that the current system is the only viable one, thereby only serving the interests of those who do well by this system. Beyond the Invisible Hand challenges readers to fundamentally rethink the assumptions underlying modern economic thought and proves that a more equitable society is both possible and sustainable, and hence worth striving for.s
Keywords: Economics